Coase-Theorem und Organ-Transplantation: Was spricht für die Widerspruchslösung? - Ingo Pies; Matthias Georg Will (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2011)
In Deutschland klaffen Angebot und Nachfrage von Spendeorganen weit auseinander. Das Spendenaufkommen hängt wesentlich vom institutionellen Regime ab, innerhalb dessen Transaktionskosten die Allokation maßgeblich bestimmen. Mit dem Coase-Argument ist dies ersichtlich, nicht aber mit dem Coase-Theorem. – – Gerrmany experiences a huge discrepancy between the demand and supply of organs suitable for transplantation. The number of organs depends crucially on the institutional regime and its transaction cost properties. These allocative effects can be seen from the theoretical perspective of the “Coase argument”, while the famous “Coase theorem” exactly here has a blind spot.
urn:nbn:de:gbv:3:2-11669
Keywords: 330; Coase-Theorem; Regulierung; externe Effekte; Gesundheitssektor; Organtransplantation; Coase theorem; regulation; external effects; health sector; organ transplantation; Organtransplantation; Coase-Theorem; Deutschland